Food allergies : a complete guide for eating when your life depends on it - Sicherer, Scott H.; Acebal, Maria Laura; Sampson, Hugh A. (Baltimore : Johns Hopkins University Press, 2013)
Posing the questions that anyone with food allergies will think to ask, this book provides practical, emotional, and scientific guidance on the topics that affect your life. Allergy expert Scott H. Sicherer addresses the full spectrum of food allergies, from mild to life threatening, from single foods to food families, clearing up misconceptions along the way. He explains how exposure to foods can bring about an allergic response, describes the symptoms of food allergy, and illuminates how food allergies develop. He also recommends tests for diagnosing both food allergies and chronic health problems caused by food allergies, such as eczema, hives, and respiratory and gastrointestinal symptoms. Food Allergies explains how to prevent exposure to a known allergen at home, at school, in restaurants, and elsewhere and what to do if exposure occurs, including how to handle an anaphylactic emergency. Dr. Sicherer also reviews food reactions that are not allergic (such as lactose intolerance), advises how to get adequate nutrition when you must avoid dietary staples, and discusses whether allergies ever go away.
What are the basic facts about food allergy? -- What do I need to tell the doctor to help get a food allergy diagnosis? -- These food allergy tests are confusing! What do they mean? -- What is anaphylaxis and how do I treat it? -- What chronic health problems are caused by food allergy? -- How do I avoid allergic reactions to food? -- How do I manage a food allergy while living a normal and healthy lifestyle, with adequate nutrition? -- Will these food allergies ever go away? -- Is there any way to prevent food allergies? -- Will there be a cure or better treatment of food allergy? -- How do I get more help and information to manage food allergies?
Includes bibliographical references (pages 270-271) and index.
Keywords: Food allergy -- Diet therapy; Food allergy -- Diet therapy; Allergies -- Diet therapy; Food Hypersensitivity -- therapy; Nonfiction